Emerging Technology Entrepreneurship Trends And Performance Multinational Organisations in Nigeria - Abu, Zekeri; Oluwaseun Oluwadamilare Oluwasanmi,; Ibrahim, Kayode Muhammed (Journal of Technology Management and Business, 2025)
Despite the key role in driving economic development using investment by multinational organisations, such as the creation of jobs, and technology transfer, many multinational organisations in Nigeria face infrastructure shortfall, weak institutional setup, and socio-economic instability. This study aims to examine emerging technology entrepreneurship trends and the performance of multinational organisations in Nigeria by closing these gaps by exploring the link between entrepreneurial orientation, technology infrastructure, human capital and the performance of multinational organisations in Nigeria. The study adopts a descriptive survey design to investigate the impact of emerging technology entrepreneurship trends on the performance of multinational organisations. The study targets operational and managerial employees of multinational companies in the telecommunication sector with subsidiaries in Osun State, Nigeria. The study employs a systematic random sampling technique. Given the infinite population approach, the sample size is predetermined as 385 respondents based on Cochran's formula (1977). A structured questionnaire was designed to gather relevant information. Descriptive and inferential statistics were utilised in the study for the data techniques. The results reveal that entrepreneurial orientation significantly impacts the performance of multinational organisations. Technology infrastructure was not statistically significant and human capital emerged as a critical predictor of organisational performance. The research recommended that multinational organisations operating in emerging markets, such as Nigeria, should tailor their strategies to address local challenges.